Functions and Values of Education in the Tunggu Betunggu Traditional Ceremony: Efforts to Preserve Local Wisdom of the Serawai Tribe in Bengkulu, Indonesia - Friantary, Heny; Sarwono, Sarwit; Yulistio, Didi (Journal of Pedagogy and Education Science, 2025)
This study aims to understand the function and educational values ​​contained in the Tunggu Betunggu traditional ceremony in the Serawai Tribe community in Simpang Village, Bengkulu Province, Indonesia. The study uses a qualitative descriptive method with a folklore approach to explore the cultural and social meaning of the tradition. Data were collected through interviews, observations, and documentation. The results of the study show that the Tunggu Betunggu ceremony not only functions as a religious ritual but also as an educational medium that conveys divine, social, and moral values ​​to the younger generation. The value of divine education is reflected in the practice of praying and giving thanks, which strengthens the spiritual relationship with God. Social values ​​include cooperation, sharing sustenance, and harmony, which strengthens solidarity and harmony in society. Meanwhile, moral values ​​are taught through respect for ancestors, respect for others, and responsibility. This ceremony plays an important role in preserving cultural identity, strengthening social solidarity, and shaping the moral character of the next generation of the Serawai Tribe.